2015
DOI: 10.1086/679665
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater–surface-water interactions: perspectives on the development of the science over the last 20 years

Abstract: Freshwater Science published a special series of papers on groundwater-surface-water (GW-SW) interactions in this issue (2015), marking the anniversary of an earlier special series of papers on the hyporheic zone published in 1993. In this concluding paper, I compare the 2 special series of papers and use this comparison to examine the development of the science in the years between 1993 and 2015. The 1993 papers marked the beginning of a period of exponential growth in the study of, and publication of, papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…These papers served several purposes: they presented testable conceptual models about ecological processes in hyporheic zones, they identified knowledge gaps that were impeding progress, and they advised researchers to focus on hyporheic hydrology to maximize progress. In the concluding paper of our 2015 series, Wondzell (2015) assessed the current state of GW-SW science (as represented by the papers in our special series) in terms of the concepts, gaps, and advice set out in the 1993 series. The 2 collections of papers are quite different.…”
Section: Ecology and Biogeographymentioning
confidence: 99%
See 2 more Smart Citations
“…These papers served several purposes: they presented testable conceptual models about ecological processes in hyporheic zones, they identified knowledge gaps that were impeding progress, and they advised researchers to focus on hyporheic hydrology to maximize progress. In the concluding paper of our 2015 series, Wondzell (2015) assessed the current state of GW-SW science (as represented by the papers in our special series) in terms of the concepts, gaps, and advice set out in the 1993 series. The 2 collections of papers are quite different.…”
Section: Ecology and Biogeographymentioning
confidence: 99%
“…Despite that, the "fact" that GW-SW interactions are important throughout stream networks is now widely accepted, and claims of this importance are rarely questioned. Wondzell (2015) concluded that a critical need still exists to develop a holistic understanding of how GW-SW interactions vary among streams types and sizes and with changes in discharge over seasons or during storm events. This knowledge would help us understand where, when, and how GW-SW interactions influence (or do not influence) the ecology of surface waters and ground waters.…”
Section: Ecology and Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been a topic of interest in hydrology because of its importance in understanding hydrologic processes, which play a crucial role in water resources management [16][17][18]. In recent years, it has increasingly been used as tracers to investigate groundwater-surface water interaction [19,20] and a separate base flow from storm runoff or annual stream flows [21]. Figure 1 shows the components of the measured seepage flow out of a rock-fill dam considering the rainfall [18].…”
Section: Introductionmentioning
confidence: 99%
“…In a heterogeneous medium, connectivity of pores will vary spatially. Well-connected pores form mobile, advection-dominated flow domains, whereas poorly connected pores form less-mobile domains where exchange may be dominated by either molecular diffusion or relatively slow advection (Berkowitz, Cortis, Dentz, & Scher, 2006; Day-Lewis, Linde, Haggerty, Singha, & Briggs, 2017;Feehley, Zheng, & Molz, 2000;Wheaton & Singha, 2010;Wondzell, 2015). These coupled but functionally different porosity domains result in a spectrum of solute residence times in the hyporheic zone that may show power-law distribution in channel return flow (Aubeneau, Hanrahan, Bolster, & Tank, 2014;Cardenas, 2015;Cardenas, Cook, Jiang, & Traykovski, 2008;Gooseff, McKnight, Runkel, & Vaughn, 2003;Haggerty, Wondzell, & Johnson, 2002).…”
Section: Introductionmentioning
confidence: 99%